2020
DOI: 10.1016/j.amjoto.2020.102721
|View full text |Cite
|
Sign up to set email alerts
|

Xerostomia, gustatory and olfactory dysfunctions in patients with COVID-19

Abstract: Background The novel Coronavirus Disease-19 (COVID-19) continues to have profound effect on global health. Our aim was to evaluate the prevalence and characterize specific symptoms associated with COVID-19. Methods This retrospective study included 326 patients with confirmed SARS-CoV-2 infection evaluated at the Emergency Department of the Umberto I Polyclinic Hospital, Rome, Italy between March 6th and April 30th, 2020. In order to assess xerostomia, olfactory and gus… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

5
100
0
3

Year Published

2021
2021
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 76 publications
(116 citation statements)
references
References 17 publications
5
100
0
3
Order By: Relevance
“…Symptoms often persist for 4–6 weeks, affecting patients' overall quality of life [ [18] , [19] , [20] ]. While early studies demonstrate a high rate of spontaneous resolution, the residual 10% with persistent olfactory dysfunction underscore the tremendous need for improved treatment options [ 21 ]. Rhinology expertise in post-viral olfactory disorders is critical for the continued development of objective screening measures and treatments for these debilitating sequelae [ 22 ].…”
Section: Taste and Smellmentioning
confidence: 99%
“…Symptoms often persist for 4–6 weeks, affecting patients' overall quality of life [ [18] , [19] , [20] ]. While early studies demonstrate a high rate of spontaneous resolution, the residual 10% with persistent olfactory dysfunction underscore the tremendous need for improved treatment options [ 21 ]. Rhinology expertise in post-viral olfactory disorders is critical for the continued development of objective screening measures and treatments for these debilitating sequelae [ 22 ].…”
Section: Taste and Smellmentioning
confidence: 99%
“…Several studies of self-reported complaints of COVID-19 patients have documented oral symptoms such as dry mouth and dysgeusia [ 4 , 5 ]. Few authors have suggested that SARS-CoV-2 binds to ACE-2 receptors on the epithelium of salivary glands, replicate, lyse cells, and propagate signs and symptoms, such as discomfort, inflammation, and pain in major salivary glands and resulting in chronic sialoadenitis [ 2 , 3 ].…”
mentioning
confidence: 99%
“…Few authors have suggested that SARS-CoV-2 binds to ACE-2 receptors on the epithelium of salivary glands, replicate, lyse cells, and propagate signs and symptoms, such as discomfort, inflammation, and pain in major salivary glands and resulting in chronic sialoadenitis [ 2 , 3 ]. Some authors have suggested that the dry mouth results from the neurotoxic effects of the virus on target organs with effects on CNS [ 4 ].…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…7,8 Anosmia is one of the clinical manifestations in COVID-19 infection and has been reported in adult population in the literature with limited data for children. [9][10][11][12] The aim of this study was to evaluate the epidemiological characteristics, as well as clinical findings of children with anosmia in COVID-19positive pediatric patients.…”
Section: Introductionmentioning
confidence: 99%